Characterization of Copper (Ii) Biosorption by Brown Algae Durvillaea Antarctica Dead Biomass - Pizarro-Konczak, J; Ortiz-Calderon, C; Castillo-Castillo, X; Barros-Vasquez, D (Springer New York LLC, 2015)
In this study we analyze the Cu(II) biosorption characteristics of the dead biomass of the Chilean brown macroalgae Durvillaea antarctica as a function of initial metal ion concentration and pH. We determined an equilibrium time of 120 min and a maximum biosorption performance at pH 5.0. The isotherms data at optimum pH best fitted with the Dubinin–Radushkevish model, showing a maximum capacity for Cu(II) biosorption of 1.44 mmol g−1. A quantitative analysis by potentiometric titrations was performed to determine different acid–base properties of the biomass surface and a FTIR analysis was performed to identify the key functional groups present on the biomass. We found characteristic peaks corresponding mainly to amine, carboxylate, hydroxyl and sulphonate moieties. A time course FTIR analysis of interaction between the biomass and Cu(II) in aqueous solution was performed to estimate sequential steps of functional groups interactions, and a SEM analysis was performed to observe the textural properties of D. antarctica biomass surface. The value of the total cation exchange capacity supports an ion exchange mechanism for the adsorption of Cu(II) by the biomass, characterized as an physisorption phenomena in a multilayer heterogeneous system. © 2015, Springer Science+Business Media New York.